2020
DOI: 10.1016/j.bmc.2020.115664
|View full text |Cite
|
Sign up to set email alerts
|

Recent advances in the design of RAR α and RAR β agonists as orally bioavailable drugs. A review

Abstract: Graphical abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 44 publications
0
10
0
Order By: Relevance
“…Given the unmet demand for anti‐ALD drugs 69 and growing evidence of the therapeutic potential of newer generation RAR‐specific agonists, 70 our data support a novel approach for prevention of ALD progression with synthetic agonists for RARβ2 23 …”
Section: Discussionmentioning
confidence: 78%
“…Given the unmet demand for anti‐ALD drugs 69 and growing evidence of the therapeutic potential of newer generation RAR‐specific agonists, 70 our data support a novel approach for prevention of ALD progression with synthetic agonists for RARβ2 23 …”
Section: Discussionmentioning
confidence: 78%
“…This RARγ-selective activity profile is quite different from the RARαselective profile of benzanilide-type retinoids such as Am80 (3) and 4. Though clinical applications of RARγ ligands have been less well investigated compared to those of RARα and RARβ ligands, [30] RARγ ligands do have therapeutic potential. [31][32][33][34][35] Compound 24 c might be a promising lead compound for RARγ-selective ligands.…”
Section: Discussionmentioning
confidence: 99%
“…69,70 Moreover, it has been shown that binding of drugs to this transcription factors can impact its activity and consequently modulate cell functions. 71 Similarly, several studies also identified several molecules presenting high affinity for HNF4α affecting its activity. 72 Therefore, it could be suggested that epicatechin metabolites by interacting with these proteins will modulate their activities, resulting in changes in the expression of identified genes and exert their health properties.…”
Section: Papermentioning
confidence: 96%